A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae) - Walsh, Jonathan H.; Ebert, David A. (Zootaxa, 2007)
Squatinids are quite distinct from other shark-like fishes, but individual species are difficult to differentiate. Four of the 16 known, valid squatinid species occur in the western North Pacific (WNP). Differences among the WNP species complex have traditionally relied upon the nasal barbel shape, interorbital and interspiracle distances, ocellus patterns, number of dermal folds about the mouth, and the presence of midback thorns. Unfortunately, many of these characters are difficult to distinguish, hindering identification of individuals. Using WNP squatinid specimens and photographs, both from field expeditions and museums, we confirm the validity of four species in the area. Additionally, we correct mistakes made in the literature on S. formosa type material, clarify differences in the particularly challenging distinction between S. formosa and S. nebulosa, and provide the basis for a revised dichotomous key for the region that includes all four known valid WNP squatinid species.